2020
DOI: 10.3233/jad-200286
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Manipulations Affect Tau Oligomerization

Abstract: Background: Mitochondrial dysfunction and tau aggregation occur in Alzheimer’s disease (AD), and exposing cells or rodents to mitochondrial toxins alters their tau. Objective: To further explore how mitochondria influence tau, we measured tau oligomer levels in human neuronal SH-SY5Y cells with different mitochondrial DNA (mtDNA) manipulations. Methods: Specifically, we analyzed cells undergoing ethidium bromide-induced acute mtDNA depletion, ρ0 cells with chronic mtDNA depletion, and cytoplasmic hybrid (cybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…It has been shown that these changes may result from mtDNA (mitochondrial DNA) disturbances. Cybrid cell lines containing mtDNA from AD patients, as well as cell lines characterized by chronic and acute mtDNA depletion, were found to have higher levels of total tau and TauOs and increased tau phosphorylation on serine 199 [102]. Lowering mtDNA levels can also trigger an adaptive stress response or adaptive metabolic reprogramming.…”
Section: Impairment Of Energy Production In the Neuronmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that these changes may result from mtDNA (mitochondrial DNA) disturbances. Cybrid cell lines containing mtDNA from AD patients, as well as cell lines characterized by chronic and acute mtDNA depletion, were found to have higher levels of total tau and TauOs and increased tau phosphorylation on serine 199 [102]. Lowering mtDNA levels can also trigger an adaptive stress response or adaptive metabolic reprogramming.…”
Section: Impairment Of Energy Production In the Neuronmentioning
confidence: 99%
“…Lowering mtDNA levels can also trigger an adaptive stress response or adaptive metabolic reprogramming. For example, Weidling et al [102] showed that cytochrome oxidase (COX) activity is proportional to mtDNA copy number. The authors also showed that dysregulation of the respiratory chain caused by mtDNA disturbances induces the accumulation of TauOs in mitochondria.…”
Section: Impairment Of Energy Production In the Neuronmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). The ρ0 cells are deviod of detectable mtDNA and have no mitochondrial oxygen consumption as previously described [23]. We examined Aβ secretion from SH-SY5Y control cells and SH-SY5Y ρ0 cells.…”
Section: Resultsmentioning
confidence: 99%
“…While the use of human cybrids are commonly used to study mitochondrial dysfunction in neurodegenerative disorders such as Alzheimer's (Onyango et al, 2006;Yu et al, 2016Yu et al, , 2017Weidling et al, 2020), and Parkinson's disease (Keeney et al, 2009;Cronin-Furman et al, 2013;Reeve et al, 2015;Pignataro et al, 2017), there is a paucity of cybrid research in BD and other psychiatric disorders. Munakata et al (2004) reported that the m.3644T > C variant in the mt-ND1 gene was associated with BD and 3644C cybrids exhibited mitochondrial dysfunction including decreases in mitochondrial membrane potential (MMP) and complex I activity compared to 3644T cybrids.…”
Section: Oxidative Phosphorylation Dysregulation In Bipolar Disordermentioning
confidence: 99%